Penerapan Strategi Brain-Based Learning Berbantuan Geogebra Terhadap Kemampuan Berfikir Kreatif Siswa - Sari, Suci Lupita; Hidayati, Destia Wahyu; Wahyuni, Arie (Square : Journal of Mathematics and Mathematics Education, 2019)
The purpose of this study is to determine the average mathematical creative thinking ability of students by using Geogebra-assisted Brain-Based Learning strategies more than KKM (70) and to find out the average mathematical creative thinking ability of students using more Brain-Based Learning strategies assisted by Geogebra higher than students' creative mathematical thinking abilities using conventional methods. This research uses quantitative methods. The sample of this study was students of class VIII-A as many as 16 students as the experimental class and class VIII-B as many as 18 students as the control class. The results of this study indicate that students' creative thinking abilities using Geogebra-assisted Brain-Based Learning strategies are more than 70 and there are significant differences between the abilities of students who obtain conventional learning with students who learn with the Geogebra-Aided Brain-Based Learning model.Â